Development of Wonosoco Village as a Fair, Healthy, and Productive Tourism Village in Kudus Regency - Jauhar, Muhamad; Fanani, Zaenal; Etikasari, Ria; Maulana, Bonnix Hedy; Novitasari, Arina; Putra, M. Adib Jaharii Dwi; Pusparatri, Edita; Sukoharjanti, Bintari Tri; Nasriyah, Nasriyah; Ariyanto, Andhika; Muslim, Ahmad Suriyadi (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
The development of Wonosoco Village as a fair, healthy, and productive tourist village in Kudus Regency has the potential to provide benefits for the community and enrich the tourism industry in the area. This activity aims to understand policies, clean and healthy living behavior, and marketing strategies, and empowerment of community businesses in tourist villages. This activity was carried out in November 2023 in Wonosoco Village, Undaan District, Kudus Regency. This activity was attended by 16 people consisting of village government, health cadres, youth groups, tourism awareness groups, and religious leaders. Delivery of material uses interactive lecture and focus group discussions in 3 sessions of 30 minutes/session. The material provided includes tourism village development policies, clean and healthy living behavior in public places, marketing strategies, and empowerment of community businesses in tourist villages. Service providers carry out assessments and evaluations using questionnaires on knowledge of clean and healthy living behavior in public places and perceptions of community participation in developing tourist villages. Data analysis is interpreted descriptively. The majority of the community has good knowledge about clean and healthy living behavior in public places (87%) and a perception of community participation in developing Wonosoco Village as a Tourism Village (50%). This activity is the first step in developing a just, healthy, and productive tourist village so it requires follow-up from local stakeholders. This follow-up takes the form of assisting in the development of tourist villages, monitoring and evaluating the success of developing tourist villages that are just, healthy, and productive.